2019
DOI: 10.1016/j.ejpn.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of observational studies in supporting extrapolation of efficacy data from adults to children with epilepsy — A systematic review of the literature using lacosamide as an example

Abstract: article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). trials in the generalised epilepsy setting, and the importance of studies in the real-life setting and of analysing efficacy data per generalized seizure type and syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This is demonstrated by Arzimanoglou et al where they concluded that there is sufficient literature and data on extrapolating lacosamide dosing to pediatric populations with FOS but the feasibility of extrapolation was difficult in the setting of other epilepsy types. 94 Third, ASMs are generally titrated to effect in clinical practice and it is often difficult to collect this information with sparse sampling and opportunistic studies. Unless a patient is taking a narrow therapeutic index drug such as phenobarbital or phenytoin, where drug levels are associated with efficacy and toxicity, most ASMs may have a limited correlation between plasma concentrations and efficacy or toxicity.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is demonstrated by Arzimanoglou et al where they concluded that there is sufficient literature and data on extrapolating lacosamide dosing to pediatric populations with FOS but the feasibility of extrapolation was difficult in the setting of other epilepsy types. 94 Third, ASMs are generally titrated to effect in clinical practice and it is often difficult to collect this information with sparse sampling and opportunistic studies. Unless a patient is taking a narrow therapeutic index drug such as phenobarbital or phenytoin, where drug levels are associated with efficacy and toxicity, most ASMs may have a limited correlation between plasma concentrations and efficacy or toxicity.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…This is demonstrated by Arzimanoglou et al. where they concluded that there is sufficient literature and data on extrapolating lacosamide dosing to pediatric populations with FOS but the feasibility of extrapolation was difficult in the setting of other epilepsy types 94 . Third, ASMs are generally titrated to effect in clinical practice and it is often difficult to collect this information with sparse sampling and opportunistic studies.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Because of the methodological and ethical challenges associated with randomized, placebo-controlled trials in children, ASMs are typically first tested and licensed in adults, and it may take years before a new drug is approved in children and infants (6,(13)(14)(15)(16). Off-label ASM use in children is therefore common (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%